2020
DOI: 10.1186/s12954-020-00382-3
|View full text |Cite
|
Sign up to set email alerts
|

Motivations, facilitators and barriers to accessing hepatitis C treatment among people who inject drugs in two South African cities

Abstract: Background: Treatment of hepatitis C (HCV) among people who inject drugs (PWID) is a critical component of efforts to eliminate viral hepatitis. A recent study found high HCV prevalence among PWID in two cities, Pretoria (84%) and Cape Town (44%). Very few (< 5%) HCV-infected individuals attended follow-up appointments. This substudy explores differences between stated desire for cure and appointment attendance in light of perceived facilitators and barriers to HCV treatment and care access among PWID. Method:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
(40 reference statements)
1
16
0
Order By: Relevance
“…This HCVST study has shown that evaluated prototype blood-based HCVST kits exhibit high usability in the hands of untrained lay-users, with respect to their usability index, contrived results interpretation, and direct user feedback. Although there are no other published usability assessments of blood-based HCVST to give context to these results, our findings are in agreement with high usability scores for HIVSTs in similar settings [ 35 , 38 , 39 , 40 ]. Given the high usability of these prototype HCVSTs, and their potential to remove barriers to traditional HCV testing, these findings are useful in informing the improved development of blood based HCVST kits towards SRA approval.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This HCVST study has shown that evaluated prototype blood-based HCVST kits exhibit high usability in the hands of untrained lay-users, with respect to their usability index, contrived results interpretation, and direct user feedback. Although there are no other published usability assessments of blood-based HCVST to give context to these results, our findings are in agreement with high usability scores for HIVSTs in similar settings [ 35 , 38 , 39 , 40 ]. Given the high usability of these prototype HCVSTs, and their potential to remove barriers to traditional HCV testing, these findings are useful in informing the improved development of blood based HCVST kits towards SRA approval.…”
Section: Discussionsupporting
confidence: 89%
“…For HCV, barriers to testing include stigma and discrimination, which suggests that the privacy offered by HCVSTs may facilitate testing [ 9 ]. In South Africa specifically, a recent study among PWID identified barriers to accessing HCV treatment as fear of stigma, and long waiting periods [ 40 ], both barriers that can be facilitated by the speed, privacy and convenience offered by HCVST. HCVSTs have the potential to remove barriers linked with traditional HCV testing, so obtaining SRA approval for HCVSTs will help reach the 2030 targets [ 1 , 9 , 40 ], especially in key populations, like PWID.…”
Section: Discussionmentioning
confidence: 99%
“…The stigma toward people who use opioids and how this serves as a barrier to effective treatment for opioid use disorders is well-described in the literature prior to the COVID-19 pandemic ( 13 ). Regarding these specific countries, there is evidence from the literature prior to the COVID-19 pandemic that stigma toward opioid users is a barrier to access to treatment ( 14 – 16 ). However, establishing a Healthline helpline to facilitate testing and treatment seems to have reduced the stigma around access for service users in New Zealand ( 17 ).…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 99%
“…Consequently, stigma and discrimination towards people who use drugs is widely accepted in healthcare facilities. This includes denial of care, conditional access to care, shaming, lack of confidentiality and privacy and being made to wait disproportionately long periods for services (Shelly et al, 2017, Versfeld et al, 2020. Moreover, there are currently no effective accountability mechanisms within healthcare facilities to manage these rights abuses, nor is there easy access to legal recourse for people who use drugs whose rights have been violated (tb hiv Care and StopTB Partnership, 2018).…”
Section: 2mentioning
confidence: 99%